IMPLICATIONS OF INDONESIAN CONSTITUTIONAL COURT RULING NO. 46/PUU-VIII/2010 ON THE CIVIL RELATIONS OF CHILDREN BORN OUT OF WEDLOCK: A MAQASHID ASY-SYARIAH PERSPECTIVE - Muhammad Luthfi; Yaris Adhial Fajrin; Khusnul Rofida Novianti (Universitas Syiah Kuala, 2023)
This article delves into the implications of the Constitutional Court's decision on Law Number 1 of 1974 through the lens of Maqashid Asy-Syariah, aiming to comprehend its impact on gender equality within Indonesian marriage law, aligning with the principles of Maqashid Asy-Syariah. Employing a normative legal research method with a legislative approach, the study analyzes legal norms, drawing from relevant legal documents and literature as data sources. The descriptive-normative data analysis method is applied to articulate the implications of the Constitutional Court's decision from the Maqashid Asy-Syariah perspective and its consequential effects on Indonesian marriage law. This pivotal decision reinterprets Article 43, paragraph (1), enabling children born out of wedlock to establish a civil relationship with their fathers. This alteration serves to protect individual rights, uphold principles of justice, ensure family welfare, and synchronize state and religious laws. Furthermore, the decision abolishes discriminatory polygamy provisions and equalizes age limits for marriage between men and women, fostering gender equality. This move not only safeguards individual rights, particularly those of women but also upholds the principles of justice, equality, and social welfare within the Maqashid Asy-Syariah framework.